Monster's ball - Daniels, Lee, 1959-; Addica, Milo; Rokos, Will; Forster, Marc, 1969-; Thornton, Billy Bob; Ledger, Heath, 1979-2008; Berry, Halle; Diddy, 1969-; Mos Def (Rapper); Calhoun, Coronji; Boyle, Peter, 1935-2006; Schaefer, Roberto (Lions Gate signature series, 2002)
Hank and Leticia inhabit stark, queasy realities of the contemporary South, he as a death row corrections officer and she as the soon-to-be widow of an inmate whose execution Hank helps conduct. In the aftermath of the execution, both lose their children to tragic deaths and they form an unlikely bond.